Friction-induced vibration and dynamic friction laws: Instability at positive friction–velocity-characteristic. (December 2015) - Graf, M.; Ostermeyer, G.-P.
Abstract: Sliding friction can lead to unstable vibration. This vibration can be unwanted, e.g. brake noise, or wanted, e.g. in violin strings. Several excitation mechanisms of friction-induced vibration are known, but still not all excitations observed in practice can be explained. Moreover, many experiments show that friction itself is highly dynamic and is by far more complex than a friction law with velocity-dependency implies. We show how the stability of an oscillator sliding on a belt will change, if a dynamic friction law with inner variable is considered instead of a velocity-dependent coefficient of friction. Unstable vibration can even be found in the case of a positive velocity-dependency of the coefficient of friction. Abstract : Highlights: We investigate an established dynamic friction law interacting with an oscillator. The system shows a new excitation mechanism for friction-induced vibration. The instability occurs although the coefficient of friction increases with velocity. The instability region is investigated by an analytical and by a numerical study. The discovered mechanism can be applied in the NVH-analysis, e.g. in brake systems.